Influence of edaphic conditions and persistent organic pollutants on earthworms in an infiltration basin. (1st July 2022) - Fernandes, G.; Roques, O.; Lassabatère, L.; Sarles, L.; Venisseau, A.; Marchand, P.; Bedell, J.-P.
Abstract: In recent decades, stormwater management has developed to allow stormwater to infiltrate directly into the soils instead of being collected and routed to sewer systems. However, during infiltration, stormwater creates a sediment deposit at the soil surface as the result of high loads of suspended particles (including pollutants), leading to the settlement of sedimentary layers prone to colonization by plants and earthworms. This study aims to investigate the earthworm communities of a peculiar infiltration basin and investigate the influence of edaphic conditions (water content, organic matter content, pH, height of sediment) and of persistent organic pollutants (POPs: PCBs, PCDDs and PCDFs) on these earthworms. Attention was paid to their age (juveniles or adults) and their functional group (epigeic, endogeic, anecic). We found that the earthworm abundance was mostly driven by edaphic conditions, with only a slight impact of POPs, with a significant negative impact of PCBDLno for juveniles and endogeic, and PCDDs for epigeic. On the contrary, the height of the sediment and the water content are beneficial for their presence and reproduction. Furthermore, POPs contents are also linked to physicochemical parameters of the sediment. Bioaccumulation was clearly revealed in the studied site but does not differ between juveniles and adults, except for PCDDs. Conversely, BAF values seemed to vary between functional groups, except for PCBDL non-ortho. It strongly varies with the family types (PCBs versus PCCD/Fs) and between congeners within the same family, with specific strong bioaccumulation for a few congeners. Graphical abstract: Image 1 Highlights: Characterization of earthworm communities in an infiltration basin with POPs. Earthworm density high with a large spatial variability. Earthworm density more related to edaphic conditions than POPs contents. But, some POPs have significant negative effect on some earthworm groups. Bioaccumulation factor moderate with high values for certain POPs and congeners.